Stabilizing volatile liquid chemicals using co-crystallization1. Issue 12 (11th February 2015) - Aakeröy, Christer B.; Wijethunga, Tharanga K.; Benton, Joshua; Desper, John
<x xml:space="preserve">Abstract</x> A convenient, effective, and scalable protocol for stabilizing volatile liquid chemicals is reported.